2015
DOI: 10.1021/acs.jpcb.5b07293
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Caged Molecule Dynamics to JG β-Relaxation II: Polymers

Abstract: At temperatures below the nominal glass transition temperature Tgα, the structural α-relaxation and the Johari-Goldstein (JG) β-relaxation are too slow to contribute to susceptibility measured at frequencies higher than 1 GHz. This is particularly clear in the neighborhood of the secondary glass transition temperature Tgβ, which can be obtained directly by positronium annihilation lifetime spectroscopy (PALS) and adiabatic calorimetry, or deduced from the temperature at which the JG β-relaxation time τβ reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 128 publications
14
74
0
Order By: Relevance
“…1 also contains results from BLS, 36 neutronscattering mean-squared-displacement (MSD), 37 and deuteron nuclear magnetic resonance ( 2 H-NMR) spin-lattice relaxation 38 measurements on ortho-terphenyl (OTP), and neutron-scattering MSD, 39 positron spectroscopy (PS), 40,41 quasi-elastic light scattering (QELS), 39 and dielectric spectroscopy 42 for polymethyl methacrylate (PMMA), which exhibit the same temperature-dependent behaviour as described for sorbitol, although with different values for T ga and T gb . It is important to comment that as noted previously, 18,19 these data represent the detection of T ga and T gb across timescales spanning over 15 orders of magnitude, indicating that a fundamental link between the processes must exist.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…1 also contains results from BLS, 36 neutronscattering mean-squared-displacement (MSD), 37 and deuteron nuclear magnetic resonance ( 2 H-NMR) spin-lattice relaxation 38 measurements on ortho-terphenyl (OTP), and neutron-scattering MSD, 39 positron spectroscopy (PS), 40,41 quasi-elastic light scattering (QELS), 39 and dielectric spectroscopy 42 for polymethyl methacrylate (PMMA), which exhibit the same temperature-dependent behaviour as described for sorbitol, although with different values for T ga and T gb . It is important to comment that as noted previously, 18,19 these data represent the detection of T ga and T gb across timescales spanning over 15 orders of magnitude, indicating that a fundamental link between the processes must exist.…”
Section: Resultssupporting
confidence: 61%
“…Additionally, the absolute values of T g are known to be slightly dependent on the heating/cooling rate as well as the thermal history of the sample, 35 however in the case of this study these relatively minor temperature shifts were minimised by using very slow cooling rates as well as the lack of significance on the overall aim of this work, which is related to the universality of the observed phenomena. Furthermore, to highlight that the results presented in this work are not simply confined to small-molecule or hydrogen bonded systems like sorbitol, and as originally suggested based on previous reports, 18,19 Fig. 1 also contains results from BLS, 36 neutronscattering mean-squared-displacement (MSD), 37 and deuteron nuclear magnetic resonance ( 2 H-NMR) spin-lattice relaxation 38 measurements on ortho-terphenyl (OTP), and neutron-scattering MSD, 39 positron spectroscopy (PS), 40,41 quasi-elastic light scattering (QELS), 39 and dielectric spectroscopy 42 for polymethyl methacrylate (PMMA), which exhibit the same temperature-dependent behaviour as described for sorbitol, although with different values for T ga and T gb .…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…A further examination of these results and other high-frequency data on amorphous systems clearly revealed that the vitrification of JG-beta relaxation is a universal process observed across a wide size and chemistry of glass-forming systems, and that the sensitivity of the high-frequency techniques to this effect is linked to the associated changes in the caged dynamics [2,7,8].…”
Section: Introductionmentioning
confidence: 80%